Opiate agonist treatment to improve health of individuals with opioid use disorder in Lebanon - Ali Ghaddar; Zeinab Abbas; Ramzi Haddad (BMC, 2017)
Abstract Background Opioid agonist therapy has been widely used to reduce harms among individuals with opioid use disorder but its effectiveness has not been evaluated in the Middle East North African (MENA) region. This study aims to evaluate the effectiveness of a program using opioid agonist therapy in combination with psychosocial support on improving psychological and social well-being, reducing arrest, and reducing risky behavior in individuals with opioid use disorder in Lebanon. Methods A one-group pre-test post-test design study was performed at SKOUN Lebanese Addiction Centre between January 2013 and December 2014. Eighty-six out of 181 patients agreed to participate and completed the 3-month assessment and 38 concluded the 12-month assessment. Psychological (depression and anxiety, quality of life), substance dependence/abuse, behavioral (injecting behavior, sharing needles and paraphernalia), and social outcomes were evaluated at baseline, 3, and 12 months post-treatment. Results Remarkable statistical significance improvements were observed 3 months after treatment in most outcome variables including quality of life, anxiety, substance dependence, overdose, employment, and injecting behavior. Improvements were sustained 12 months after treatment. Conclusion Results support expanding the access to opioid agonist therapy in other MENA countries to treat substance dependence and reduce harms among individuals with opioid use disorder.